UPAYA MENINGKATKAN PEMAHAMAN KONSEP DAN DISPOSISI MATEMATIS MENGGUNAKAN MODEL PEMBELAJARAN TREFFINGER DI SMA NEGERI 1 ANGKOLA BARAT - Benny Sofyan Samosir; Andes Fuady Harahap (PeTeKa (Jurnal Penelitian Tindakan Kelas dan Pengembangan Pembelajaran), 2018)
his type of research is Class Action Research. Where the subject of the research is the grade X5 SMA Negeri 1 Angkola West which consists of 38 students. While the techniques and tools to capture data that is now, tests and observations. The percentage of students on mathematical disposition now cycle I was 50.26% to 81.57% in cycle II. With the amount of the percentage increase in students ' mathematical disposition of 31.31%. Understanding of the mathematical concepts of students increases, it is retrieved from the percentage of the cycle I 52.63% become 81.39% in cycle II, students and the amount of the percentage rose 28.94%. Students learn math activity increases; it is retrieved from 63.98% percentage of the cycle I and 63.98% in cycle II. With the amount of the percentage increase in the activity of students of 22.94%. The ability of the teacher to manage learning percentage amounted to 64.00% in cycle I and cycle II 83.00%, with an increase of 19.00%. The results of this study showed that the learning model Treffinger might improve the understanding of mathematical concepts and disposition of the students of class X5 SMA Negeri 1 Angkola West.Keywords: The Learning Model Treffinger, understanding Mathematical concepts, Dispositions, SPLDV.